Formulation, development and evaluation of patient friendly dosage forms of metformin, Part-III: Soluble effervescent tablets - Mohapatra, Ashutosh; Parikh, Rajesh K; Gohel, Mukesh C (Asian Journal of Pharmaceutics (AJP), 2014)
Metformin hydrochloride is an orally administered antihyperglycemic agent, used in the management of non-insulin- dependant (type-2) diabetes mellitus. Difficulty in swallowing (dysphagia) is common among all age groups, especially in elderly and pediatrics. Unfortunately, a high percentage of patients suffering from type-2 diabetes are elderly people showing dysphagia. The above problem becomes even more severe due to high dose (500–1000 mg) and need for daily intake of metformin. Thus, the above titled work was undertaken to provide patient friendly dosage form. Not only metformin is poorly compressible (Carr’s index 37), but effervescent ingredients are also poorly compressible so, method of wet granulation was used for preparation of tablets using absolute alcohol as binder. Metformin effervescent tablets were prepared using citric acid (CA), tartaric acid (TA), and treated sodium bicarbonate (heating at 120°C for 30 min), glycine, talc, sucralose, and mango flavor. Controlled heating of sodium bicarbonate formed a sheath or desiccant skin of sodium carbonate on bicarbonate nucleus leading to surface passivation which prevents onset effervescent reaction in presence of moisture leading to stability. Of all combinations, CA and TA in the molar ratio 1:2 was found to be most stable as higher amount of least hygroscopic TA protects hygroscopic CA from the attack of moisture. Also, it was found that using treated sodium bicarbonate in stoichiometric ratio gave substantially stable effervescent tablets on short term stability study (room temperature and humidity and 75% relative humidity (RH) and room temperature) as sodium carbonate preferentially absorbs moisture. All the ingredients selected were water soluble.